2021
DOI: 10.1371/journal.pntd.0009414
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on rabies reemergence in Latin America: The case of Arequipa, Peru

Abstract: In Latin America, there has been tremendous progress towards eliminating canine rabies. Major components of rabies elimination programs leading to these successes have been constant and regular surveillance for rabid dogs and uninterrupted yearly mass dog vaccination campaigns. Unfortunately, vital measures to control COVID-19 have had the negative trade-off of jeopardizing these rabies elimination and prevention activities. We aimed to assess the effect of interrupting canine rabies surveillance and mass dog … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Raynor et al reported that the yearly mass dog vaccination programme in Peru was interrupted during COVID-19, resulting in a negative effect on rabies elimination and prevention activities. 26 Fifth, decreased incidence and mortality of zoonotic diseases might be due to their own long-term downward trends, which is a confounding factor in this study. However, to avoid the interference of the long-term trend of disease itself, some analyses were conducted, including the Cox-Stuart test and Farrington surveillance algorithm.…”
Section: Discussionmentioning
confidence: 88%
“…Raynor et al reported that the yearly mass dog vaccination programme in Peru was interrupted during COVID-19, resulting in a negative effect on rabies elimination and prevention activities. 26 Fifth, decreased incidence and mortality of zoonotic diseases might be due to their own long-term downward trends, which is a confounding factor in this study. However, to avoid the interference of the long-term trend of disease itself, some analyses were conducted, including the Cox-Stuart test and Farrington surveillance algorithm.…”
Section: Discussionmentioning
confidence: 88%
“…COVID-19 pandemic has disrupted many essential health services including strategies for rabies elimination ( 32 ) with funding for non-COVID-19 disease projects redirected to control of COVID-19. These has disrupted mass dog vaccination, provision of PEP and community awareness activities ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has disrupted the lives and economies of most countries all over the world, whether directly or indirectly ( 29 ). As public health professionals are diverted to working on the pandemic, it has disrupted vaccination campaigns in countries ( 30 ), including rabies vaccination, and field training. Field staff were overloaded with COVID-19 related duties, and rabies was once again neglected ( 31 ).…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…Additionally, due to prioritization failure and supply chain disruption, many remote provinces, where rabies is often widespread ( 5 , 12 ), faced vaccine shortage ( 31 , 32 ). Due to lockdowns, fewer people were leaving home, and increased difficulty in travel to and from hospitals or clinics led to decrease in identification of suspected rabid dogs, slower dispatch of rabies response teams, and delayed removal of suspected rabid dogs ( 30 ). Lockdowns also deterred people from seeking medical attention due to fear of contracting COVID-19 or because hospitals were overflowing.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation